Kajian Literatur: Analisis Literasi Sains dan Literasi Digital Siswa SMP pada Materi Pembelajaran IPA - Arif, Rifda Nur Hikmahwati; Isra; Lestari, Dewi Ayu; Yanto, Nurfitra; Samputri, Salma (JAMBURA Elementary Education Journal, 2024)
This study is a literature review aimed at systematically analyzing previous research findings related to science literacy and digital literacy among junior high school students in the context of science education. The method used is a literature review focusing on science literacy and digital literacy. A total of 20 relevant articles and scientific journals indexed in reputable databases were collected and analyzed to derive recommendations related to the literature review. The findings indicate that the level of science literacy among junior high school students in science education is generally low to moderate, while digital literacy shows better results, ranging from moderate to high. This study concludes that the development of integrated science education with strengthened science and digital literacy is essential to enhance students' competencies in addressing the challenges of the 21st century.